6r+8s-7s-r+3r=

Simple and best practice solution for 6r+8s-7s-r+3r= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6r+8s-7s-r+3r= equation:


Simplifying
6r + 8s + -7s + -1r + 3r = 0

Reorder the terms:
6r + -1r + 3r + 8s + -7s = 0

Combine like terms: 6r + -1r = 5r
5r + 3r + 8s + -7s = 0

Combine like terms: 5r + 3r = 8r
8r + 8s + -7s = 0

Combine like terms: 8s + -7s = 1s
8r + 1s = 0

Solving
8r + 1s = 0

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-1s' to each side of the equation.
8r + 1s + -1s = 0 + -1s

Combine like terms: 1s + -1s = 0
8r + 0 = 0 + -1s
8r = 0 + -1s
Remove the zero:
8r = -1s

Divide each side by '8'.
r = -0.125s

Simplifying
r = -0.125s

See similar equations:

| 5n+-9n=-16 | | 12-3x^2=23x | | U=F(a+R) | | x-7.5=2x | | f(x)=2pi*x | | R=.66t+v | | 1.4z+2.2=2.7z-0.2 | | 5.4t+14.6-10.1t=.4(25+j) | | 5a+15b=-24 | | 4(8-5)=152 | | f(x)=13x+9 | | 7(x+2)+1=15-7x | | V-80=5 | | 2x-7y+11x-4y= | | -14=7y+64 | | 2x-4(x-3)=-4+3x-24 | | 96-u=68 | | 4t-7=4t-7 | | -2v^2-v+12=-3v^3+6v | | a-5+8=5 | | 5c-6=3c-8 | | 3(y-2)-7=12-2y+6 | | 6x+2y=42 | | 92+s=98 | | 2236000-17740x=45 | | 18+32=p-32 | | 15=21x+36 | | 2(3x-3)=(4x-2) | | (3n)(4n)= | | 2(n-3)=7k+4 | | 10x-2-5x=3x+3 | | Y=5(14)+30 |

Equations solver categories